THE TYPES OF FLOUTING MAXIM BY GOVERNOR CANDIDATES OF NORTH SUMATERA IN ELECTION DEBATE 2018 - Tri Wita Indah Sari; Zainuddin .; Amrin Saragih (Universitas Negeri Medan, 2020)
The objective of this study is to explain the reason of flouting maxim used by governor candidates of North Sumatera in election debate 2018. The research methodology used in the research is qualitative research design.The data were analyzed by using interactive model of qualitative data management and analysis namely data collection, data condensation, data display and verification and conlusion. The findings of this study revealed that the reasons reason for flouting maxim because the candidates gave implicitly response to hearer in their response. Each candidate gave the implied meaning in their response because candidates knew that they were as a rival in this debate in order to get a chance as a Governor in North Sumatera.Keywords: Debate, Governor Candidates, Flouting Maxim.